Does Multiple Capitals Disclosure Affect the Capital Market? An Empirical Analysis in an Integrated Reporting Perspective - Sun, Yanqi; Qiao, Xin; An, Yi; Fang, Qiaoling; Wu, Na (Frontiers in Psychology, 2022)
Integrated reporting (IR), as a novelty corporate reporting approach, focuses on how six forms of capital promote corporate value. This paper explores whether this kind of multiple capitals disclosure (MCD) framework has an impact on the capital market. Using a sample of Chinese A-share firms from 2012 to 2016, we examine the relationship between MCD quality and firm value. The results indicate that a higher MCD quality leads to a greater firm value. Our results are robust to a variety of sensitivity tests. Further evidence suggests that MCD quality could increase profitability by affecting the decision-making of non-financial stakeholders and enhance the value relevance of financial information by affecting the decision-making of investors. The paper helps understand how the IR approach affects the perception of investors on the value of a firm. The findings of the paper are of interest to academics, corporate management, investors, and governmental officials.